From public domain to public interest - Wilf, Steven (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2020)
This brief essay is an exploration of how the public domain came to achieve its place as a focus of attention, how it shaped a generation of scholars, and why public interest might be a more salient construct for thinking about how to foster a public-directed system of global knowledge governance. In short, this is the story of the rise, fall, and reincarnation – as public interest – of the public domain.